2017
DOI: 10.18632/oncotarget.22398
|View full text |Cite
|
Sign up to set email alerts
|

Serum SDF-1 levels are a reliable diagnostic marker of feline mammary carcinoma, discriminating HER2-overexpressing tumors from other subtypes

Abstract: The feline mammary carcinoma (FMC) is the third most common tumor in cat, sharing many clinicopathological features with human breast cancer and thus, considered a suitable model for comparative oncology. Due to its poor prognosis, further studies are required to improve the diagnostic accuracy and treatment of cats with spontaneous mammary carcinoma. Recently, it was reported that the overexpression of stromal cell-derived factor-1 (SDF-1) has great value in human breast cancer diagnosis, suggesting that diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…Staining primary tumors for Bcl-2, an anti-apoptotic protein, revealed that increased Bcl-2 positivity was associated with longer survival, disease-free survival and cancer-specific survival [49]; however only a small proportion of FMT were positive for Bcl-2 in this study, and thus this marker may only be used to prognosticate a subpopulation of feline patients. Consistent with the ability of SDF-1 to predict outcome in human patients, SDF-1 was also found to be higher in cats with FMT compared to healthy individuals, although it was unable to predict outcome [50]. Finally, sphingosine kinase-1 (SPHK1) was found to be increased in FMT vs normal mammary tissue, and levels within primary tumors correlated with grade, lymphovascular invasion, and ER negativity.…”
Section: Plos Onementioning
confidence: 53%
“…Staining primary tumors for Bcl-2, an anti-apoptotic protein, revealed that increased Bcl-2 positivity was associated with longer survival, disease-free survival and cancer-specific survival [49]; however only a small proportion of FMT were positive for Bcl-2 in this study, and thus this marker may only be used to prognosticate a subpopulation of feline patients. Consistent with the ability of SDF-1 to predict outcome in human patients, SDF-1 was also found to be higher in cats with FMT compared to healthy individuals, although it was unable to predict outcome [50]. Finally, sphingosine kinase-1 (SPHK1) was found to be increased in FMT vs normal mammary tissue, and levels within primary tumors correlated with grade, lymphovascular invasion, and ER negativity.…”
Section: Plos Onementioning
confidence: 53%
“…Furthermore, overexpression of several molecular biomarkers is also associated with poor prognosis, e.g., macrophage-stimulating protein receptor (RON), related to tumor invasion, cyclo-oxygenase (COX)-2, expressed in malignant FMCs, and topoisomerase IIβ binding protein 1 (TopBP1), which is similar to BRAC2 in HBC [ 31 , 58 ]. Interestingly, the CXCR4/CXCL12 axis, which controls cell survival, migration and proliferation, is also a key factor in feline breast cancer progression and metastasis, as reported for HBC [ 59 , 60 ], and it’s disruption is associated with lower OS time [ 60 , 61 , 62 ]. Additionally, CXCL12 has been reported as a blood serum marker in the cat, particularly for HER2-positive tumors [ 62 ].…”
Section: Feline Mammary Carcinomamentioning
confidence: 99%
“…Interestingly, the CXCR4/CXCL12 axis, which controls cell survival, migration and proliferation, is also a key factor in feline breast cancer progression and metastasis, as reported for HBC [ 59 , 60 ], and it’s disruption is associated with lower OS time [ 60 , 61 , 62 ]. Additionally, CXCL12 has been reported as a blood serum marker in the cat, particularly for HER2-positive tumors [ 62 ]. Finally, analysis of the vascular endothelial growth factor (VEGF) status, shows that this molecule is overexpressed in more aggressive carcinomas [ 50 , 63 ], playing an important role in tumor-associated angiogenesis.…”
Section: Feline Mammary Carcinomamentioning
confidence: 99%
“…The prognosis is poor to guarded for most cats with mammary carcinomas, 11 but strongly dependent on several clinical and histological factors, such as tumour size, nodal metastasis, World Health Organization (WHO) clinical stage, histological type, lymphovascular invasion, mitotic index and histological grade 1,12‐18 . Several molecular and serum markers have also been associated with prognosis, namely: the level of expression of the cyclooxygenase‐2 enzyme, human epidermal growth factor receptor‐2 (HER2), oestrogen and progesterone receptors, Ki‐67, AgNORs count, stromal cell‐derived factor‐1, programmed death ligand‐1 and cytotoxic T‐lymphocyte‐associated antigen 4 18‐26 . The clinical application of some of these markers is limited and others are only available after histological evaluation of both tumour and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%